2012
DOI: 10.1007/s11103-012-9969-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic changes and signalling pathways induced by arsenic stress in rice roots

Abstract: Arsenic (As) is considered the most common toxic metalloid, but its molecular mode of action is not well understood. We investigated whether arsenate [As(V)] can induce intracellular reactive oxygen species production and calcium oscillation in rice roots. To better understand the molecular basis of plant cell responses to As, we performed a large-scale analysis of the rice transcriptome during As(V) stress. As(V) induced genes involved in abiotic stress, detoxification pathways and secondary metabolic process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(103 citation statements)
references
References 132 publications
4
77
1
3
Order By: Relevance
“…In particular, GSTU12 (shoot), GSTU19 (root and shoot), GSTU24 (root and shoot), GSTU30 (shoot), GSTU31 (root) and GSTU39 (root) were strongly upregulated [fold change (FC) > 20] (Figure 4A). GSTU19 , GSTU24 and GSTU39 were found to be upregulated in the roots of rice seedlings under arsenate exposure using a microarray platform [67], suggesting that part of the Cd defense might be similar to the As defense in the roots of rice. Enhanced GST with glutathione peroxidase activity in transgenic tobacco increased glutathione-dependent peroxide scavenging and alterations in glutathione and ascorbate metabolism that led to reduced oxidative damage [68].…”
Section: Resultsmentioning
confidence: 99%
“…In particular, GSTU12 (shoot), GSTU19 (root and shoot), GSTU24 (root and shoot), GSTU30 (shoot), GSTU31 (root) and GSTU39 (root) were strongly upregulated [fold change (FC) > 20] (Figure 4A). GSTU19 , GSTU24 and GSTU39 were found to be upregulated in the roots of rice seedlings under arsenate exposure using a microarray platform [67], suggesting that part of the Cd defense might be similar to the As defense in the roots of rice. Enhanced GST with glutathione peroxidase activity in transgenic tobacco increased glutathione-dependent peroxide scavenging and alterations in glutathione and ascorbate metabolism that led to reduced oxidative damage [68].…”
Section: Resultsmentioning
confidence: 99%
“…Sulfur metabolism genes have been shown to be induced after arsenic treatments in bacteria [58], [65], yeast [44], [51], [66] and plants [63], [67], [68]. These genes include sulfate transport, sulfur assimilation and cysteine synthesis genes, which are needed in order to increase GSH contents.…”
Section: Resultsmentioning
confidence: 99%
“…A genome-wide transcript abundance study of grape ( Vitis vinifera L.) leaves under heat stress revealed upregulation of one CDPK (CF511469) and CIPK25 gene (BQ797947; Liu et al 2012 ). In another study, large-scale ESTs of abiotic stresstreated leaves, berries, and root of Vitis vinifera were generated and analyzed where transcripts encoding for CIPK10 were overrepresented in both the stressed leaf and berries clusters (Tillett et al 2011). Huang et al ( 2012 performed microarray study of early Arsenic-induced gene expression in rice and showed that along with seven calmodulin genes, two CBL genes, one CIPK gene ( OsCIPK21 ), and four CDPK genes ( OsCPK4, OsCPK13, OsCPK20 , and OsCPK21 ) were upregulated on As(V) treatment.…”
Section: Evolutionary Divergence Of Ca 2+ Kinase Gene Familiesmentioning
confidence: 99%